PAPR Reduction for Very High Throughput WLAN with Backward Compatibility to IEEE802.11 a/n - Syafei, Wahyul Amien; Ochi, Hiroshi (Transmisi, 2009)
We propose a simple technique to reduce PAPR for a Very High Throughput Wireless LAN with backward compatibility with IEEE 802.11a/n system. By applying proposed phase rotation in partial transmit sequence technique we got PAPR reduction up to 3.01dB lower than conventional one, yields in comparable PAPR with IEEE802.11n preamble. Keywords: Gigabit, Wireless LAN, backward compatibility, IEEE802.11a/n WLAN System, PAPR reduction.